2004
DOI: 10.7773/cm.v30i12.104
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of Lithothamnion muelleri (Corallinales, Rhodophyta) in the southwestern Gulf of California, Mexico

Abstract: ResumenEl alga coralina no geniculada Lithothamnion muelleri Lenormand ex Rosanoff es comúnmente encontrada formando mantos de rodolitos en zonas someras expuestas al oleaje dentro del suroeste del Golfo de California. Esta especie tiene bandas de crecimiento a todo lo largo de las ramas principales del talo que sugieren un crecimiento periódico y que probablemente podrían ser utilizadas para determinar su tasa de crecimiento y edad. Como parte de la investigación que se está desarrollando sobre los mantos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In particular, L. corallioides and P. calcareum are included in annex V of the Habitats Directive. Rhodoliths and maerl preservation is particularly important also due to the slow growth rate of coralline red algae (Frantz et al, 2000;Blake and Maggs, 2003;Rivera et al, 2004;Schäfer et al, 2011), which makes them lowly resilient to environmental stress (Grall and Hall-Spencer, 2003;Wilson et al, 2004;Nelson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, L. corallioides and P. calcareum are included in annex V of the Habitats Directive. Rhodoliths and maerl preservation is particularly important also due to the slow growth rate of coralline red algae (Frantz et al, 2000;Blake and Maggs, 2003;Rivera et al, 2004;Schäfer et al, 2011), which makes them lowly resilient to environmental stress (Grall and Hall-Spencer, 2003;Wilson et al, 2004;Nelson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Growth rates range from <1.0 mm yr −1 (reviewed in Foster 2001) to > 5.0 mm yr −1 (Steller et al 2007) depending on species and estimation technique. Direct field measurements (Adey & McKibbin 1970), changes in calcium carbonate weight (Potin et al 1990), 14 C dating (Littler et al 1991, Frantz et al 2000, Goldberg 2006), Mg:Ca ratios (Halfar et al 2000, Kamenos et al 2008, Alizarin Red staining (Blake & Maggs 2003, Rivera et al 2004, Steller et al 2007, Amado-Filho et al 2012, or a combination of these techniques (Darrenougue et al 2013) have all been used to determine growth rates and/or age. Growth is typically more rapid in summer than in winter (Adey & McKibbin 1970, Potin et al 1990, Steller et al 2007, with one report of faster growth in winter (Rivera et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Direct field measurements (Adey & McKibbin 1970), changes in calcium carbonate weight (Potin et al 1990), 14 C dating (Littler et al 1991, Frantz et al 2000, Goldberg 2006), Mg:Ca ratios (Halfar et al 2000, Kamenos et al 2008, Alizarin Red staining (Blake & Maggs 2003, Rivera et al 2004, Steller et al 2007, Amado-Filho et al 2012, or a combination of these techniques (Darrenougue et al 2013) have all been used to determine growth rates and/or age. Growth is typically more rapid in summer than in winter (Adey & McKibbin 1970, Potin et al 1990, Steller et al 2007, with one report of faster growth in winter (Rivera et al 2004). Although growth estimates are variable, all have concluded that rhodoliths are slow-growing and some may live for >100 yr (Frantz et al 2000, Rivera et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…For the setup of both experiments, healthy L. stictiforme (about 8 cm in diameter) with no signs of damage or bleaching were carefully collected (detaching their basal parts using hammer and chisel) by SCUBA diving (Figure 3A) and transported in insulated aquaria to the laboratory within one hour, where they were cleaned from epiphytes and rinsed with new seawater. Afterwards, they were placed in aquaria with oxygenators, kept at the temperature of their origin environment and stained using Alizarine-Red stain (Sigma-Aldrich, Steinheim, Germany) 0.25 g•l-1 for 24 h (Blake and Maggs, 2003;Rivera et al, 2004). The stained L. stictiforme thalli were transported to the receiving sites and glued with a twocomponent epoxy underwater filler (Sub Coat Veneziani) on granite tiles which were attached on horizontal substrates in the field (Figure 3A).…”
Section: Sampling Designs and Experiments Set Upmentioning
confidence: 99%